Nurses’ Perspectives of the Supportive Care Needs of Men with Prostate Cancer - Roula Mohammad Abboud; Nassim Samir Saker; Amal Khalaf Kadhim; Mohammad Mahdi Saeed Sahi; Hussein Kadhim Hussein; Alaa Hamza Hermis (Medical Journal of Babylon)
Background: Prostate cancer is the most common form of cancer affecting men. Perceptions of oncology nurses regarding educational needs would assist in gaining more understanding of survivor needs and ultimately provide better quality care to individuals who have completed cancer treatment. Objectives: To investigate the nurses’ point of view about the priority and the degree of importance of educational needs for prostate cancer patients. Materials and Methods: The current study used a descriptive design and was conducted at the chemotherapy and radiology center of Tishreen University Hospital in Lattakia City, Syria during 2020–2021. The study comprised 50 nurses in the chemotherapy department. Tools used in the study were adopted from the Toronto Informational Needs Questionnaire Cancer by the researchers to achieve the purpose of the study. Results: The majority of studied nurses (82%) aged between 30 and 40 years old, also about half of nurses (46%) were single, two third of nurses (66%) have preparatory degree, the highest ratio of nurses (60%) have from 1 to 5 years of experience, whereas the most of nurses (70%) have from 6 to 10 years of experience in general nursing; finally most of the nurses (78%) did not have any oncology training session. The results also found that there were a statistically significant differences in oncology nursing opinion according to their age, educational level, and years of experience in oncology nursing, whereas there were no statistically significant differences according to the marital status, years of nursing experience in general and training sessions. Conclusion: All the information needed by prostate cancer patients is of low importance from the studied nurses’ point of view except the psychological needs with moderate importance. There is a high statistically significant difference in oncology nursing opinion according to the age, educational level, and years of experience.